Identifying a gap in drowning prevention: high-risk populations. Issue 3 (6th January 2020) - Willcox-Pidgeon, Stacey M; Franklin, Richard Charles; Leggat, Peter A; Devine, Sue
Abstract : Introduction: Some populations have been less susceptible to reductions in drowning than others. It has been hypothesised that this is due to prevention strategies failing to account for the influence of social determinants (such as ethnicity, socioeconomic status). Populations such as ethnic minorities have been over-represented in injury statistics, however this is not well explored in drowning. This study aims to identify high-risk populations for drowning, risk factors and prevention strategies. Methods: A literature review undertaken systematically using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses approach was conducted of peer-reviewed literature in English, published between 1990 and 2018 from high-income countries. Search terms included drowning, water safety, ethnic minority, migrant, and culturally diverse. Results: In total, 35 articles were included. High-risk populations identified were: ethnic minorities, First Nations/Aboriginal people, migrants and rural residents. Over half (51%) focused on children (0–18 years). Risk factors included social determinants, swimming ability and knowledge, attitudes and behaviour. Four intervention studies were found; two focused on upskilling adults from high-risk populations to increase employment opportunities within the aquatic industry; an evaluation of a 10-year rock fishing safety education project and a learn-to-swim programme for minority children. Proposed prevention strategies included education, practical skills, research, policy and engagement. Discussion: Limited literature exists pertaining to drowning among adults from high-risk populations. There is a need to increase the sophistication of drowning prevention strategies addressing the disparities in drowning from a culturally appropriate perspective. Acknowledging the role of the social determinants of health in drowning prevention is essential in order to improve drowning outcomes for high-risk populations globally.